Measuring the intensity of innovation in the Brazilian food sector: A DEA-Malmquist approach - Giselle Cappellesso; Cristiano Moreira Raimundo; Karim Marini Thomé (Innovation & Management Review, 2020)
Purpose - This study aims to measure the intensity of innovation in the Brazilian food sector and compares it to other manufacturing sectors in the country. Design/methodology/approach The authors used economic and financial data provided by the annual survey of industry [Pesquisa Industrial Anual (PIAs), in Portuguese] and other supporting data provided by the survey of innovation [Pesquisa de Inovaç\~ao (PINTEC), in Portuguese] and the classification of technology intensity (TI) proposed by the Organization for Economic Co-operation and Development. The authors subsequently applied the Malmquist index in addition to the data envelopment analysis to measure innovation. Findings The results reveal that the Brazilian food sector is classified as a sector with low TI and investment in research and development (R&D), which represents one of the lowest rates when compared to other sectors. Thus, the Brazilian food sector is far from achieving its full potential. Nevertheless, the authors noticed that the sugar refinery industry showed an evolution in its technology frontier and presented a frequency of innovation similar to the average of high-tech industries. Originality/value This study contributes to the debate on innovation in the food sector, emphasizing the need to accomplish higher investments in R&D to increase the productivity of the sector.
Keywords: 650; Food sector; Innovation; Malmquist index; Manufacturing sector